Mitigation techniques for crosstalk in ICs - Mohd Razif R.A.; Mohamad Maharum S.M.; Hasani A.H.; Mansor Z. (IOP Publishing Ltd, 2023)
Electronics packaging; Integrated circuit interconnects; Timing circuits; Coupling length; Crosstalk mitigation; High-speed ICs; Mitigation techniques; Schmitt trigger; Signal Integrity; Signal wires; Crosstalk